2018
DOI: 10.1016/j.atherosclerosis.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

PDZK1 in leukocytes protects against cellular apoptosis and necrotic core development in atherosclerotic plaques in high fat diet fed ldl receptor deficient mice

Abstract: PDZK1 is required for anti-atherogenic responses in macrophages including HDL dependent protection against apoptosis and macrophage mediated efferocytosis and limits the accumulation of apoptotic cells within atherosclerotic plaques protecting against necrotic core development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…This study by Yu et al [4], along with many recent in vitro and pre-clinical animal studies, highlights the multi-facet beneficial actions of HDL, beyond cholesterol transport, in mediating atheroprotection. Moreover, decades of epidemiological evidence show that low levels of circulating HDL correlated with increased atherosclerotic disease.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…This study by Yu et al [4], along with many recent in vitro and pre-clinical animal studies, highlights the multi-facet beneficial actions of HDL, beyond cholesterol transport, in mediating atheroprotection. Moreover, decades of epidemiological evidence show that low levels of circulating HDL correlated with increased atherosclerotic disease.…”
mentioning
confidence: 78%
“…In conclusion, the study by Yu and colleagues [4,9] identify for the first time a new role for macrophage PDZK1 in protecting against apoptosis and promoting macrophage migration, ultimately reducing atherosclerotic progression. These studies have identified additional mechanisms that regulate macrophage cell death and how HDL can protect against macrophage apoptosis.…”
mentioning
confidence: 86%
See 3 more Smart Citations